PENGARUH LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN MUSI BANYUASIN - Ellisyah Mindari (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2020)
This study aims to analyze the effect of the work environment on employee productivity in the Department of Population and Family Planning of Musi Banyuasin Regency. This study uses a quantitative approach. The sample in this study is the same as the total population of 83 employees. The method of analysis uses analytical tools with the IBM SPSS Statistics 24 program. The results of this study indicate that there is a positive effect of the work environment on work productivity based on the results of simple linear regression calculations, y = 18.987 + 0.809x, the productivity variable (y) is influenced by the work environment variable (x) by 76.5% and based on test results t is obtained tcount greater than ttable is 9,457> 1,990, so it can be concluded that there is an influence of the work environment on employee work productivity at the Department of Population and Family Planning of Musi Banyuasin Regency. Keywords: Work Environment; Work Productivity; Simple Linear Regression